Os desenhos de Silva Porto no acervo artístico da SNBA : estudo e inventário científico - Antunes, Sara Beirão, 1994- (2018)
The National Society of Fine-Arts (SNBA) holds an important artistic collection in the areas of Painting, Sculpture, Engraving, Photography and Drawing. Mainly constituted by XIX and XX century art works, this collection holds valuable specimens to the Portuguese Art History. However, the absence of rigorous scientific inventory makes these works not properly known and disseminated, reason why the construction of a specialized inventory, process initiated by this work, is an urgency as far as the appreciation of this collection is concerned. In this thesis is presented the process of the scientific inventory and the study of the collection of drawings created by the artist Silva Porto, who played a very relevant role in Grémio Artístico, institution that would later become SNBA. By inventoring this collection, we hope to contribute to the knowledge of the artist’s work, poorly explored, especially regarding his relationship with Drawing. All of the three hundred and sixty-six drawings inventoried, represent an important part of the author’s estate, corresponding to about 59% of a universe of six hundred and eighteen known objects in Portugal. The study of this collection allows to identify the existence of unpublished drawings, which correspond to more than half of the total inventoried, and also compare it with other collections, both quantitatively and in terms of techniques and artistic means. On the other hand, an inventory according to museological practices gives a specific knowledge of each art work, as well as its dissemination – and the dissemination of the institution itself – both in internal SNBA events and through loans to other institutions. The collection of the physical data of each of the drawings was accompanied by a rigorous photographic survey, indispensable to the inventory process, as well as the state of conservation of the art works. The inventory of the Silva Porto’s Drawing Collection also allowed to rectify and/or update some bibliography, as well as to collect marks and inscriptions and to identify recurrent themes in the artist’s work. Because the scientific inventory is not only about the individualized knowledge of each specimen – thus serving as the basis for all future activities related to the goods – but also to ensure its safeguard and permanence, a proposal was also made concerning the preventive conservation plan for the studied collection